Імпульсне джерело високої напруги - Чміль, А. І.; Науменко, О. В. (Energy and Automation, 2017)
THE STRUCTURE OF THE HIGH VOLTAGE PULSE SOURCEA. I. Chmil, O. V. Naumenko It is looked on pulsed source of high voltage, its description, and a circuit diagram. Expressions are given for the determination of the coefficient of transformation and the output voltage of pulsed source.The department of electric drive and electrotechnologies conduct the research of the use of high electric field, which is one of the most promising means of influencing the grain mass. One of the priorities of the use of high electric field is the processing of grain for the purpose of disposal of pests of grain.In installations electrotechnological processes where high tension is applied, one of the active factors is the high electric field, that field strength of more than 100 kV/m.The aim of this work is reducing the size and material source of high voltage, expanding the boundaries of operational parameters adjustment process and improve the efficiency of processing grain.The range of the frequency of the output pulses of 1-19 kHz. Pulse duty cycle ranges from 18 to 42% at 1 kHz frequency pulses and 46 to 48% at a frequency of 19 kHz pulses.Developed and manufactured high voltage pulse power has the energy parameters: output voltage - 0 ... 30 kV maximum load current - 1,3 mA idle power - 18 watts. Established frequency energy parameters IDVN depending on the frequency of pulses.In developed pulsed high voltage source provides frequency and duration of pulses of voltage on the electrodes that provide a great variety of operational parameters of the device. Established expressions for transformation ratio and output voltage of the input voltage and frequency pulses.